2021
DOI: 10.1177/15589447211044783
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Telemedicine and Phone Consultation Effects on Rate of Hand Transfers to Trauma Centers and Specialty Services Referrals

Abstract: Background Telemedicine consultation can increase patients’ access to subspecialty care and decrease the number of unnecessary hospital transfers. In 2014, the Arkansas Hand Trauma Telemedicine Program (AHTTP) was established to extend specialized hand care throughout Arkansas. The purpose of this study is to assess whether transfers are affected when consultation with a hand specialist is performed by phone compared with using a live audiovisual consultation. Methods We reviewed data from the first year of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Effective communication and planning are the most important factors in improving the transfer process and reducing adverse events [49]. Bracey et al [50] showed that communication with a surgeon is the key factor for accurate assessment of the need for transfer to trauma centers.…”
Section: Indicators For Healthcare Services Provisionmentioning
confidence: 99%
“…Effective communication and planning are the most important factors in improving the transfer process and reducing adverse events [49]. Bracey et al [50] showed that communication with a surgeon is the key factor for accurate assessment of the need for transfer to trauma centers.…”
Section: Indicators For Healthcare Services Provisionmentioning
confidence: 99%
“…We used the FCC Mapping Broadband in America interactive tool to record the latest available internet upload and download speeds for all 3141 counties in the United States [13]. We used the FCC threshold for broadband speed, which equates to 25 Mbps for downloads and 3 Mbps for uploads [5,6]. The FCC mapping broadband public use files are considered the most comprehensive datasets describing high-speed internet infrastructure within the United States [13].…”
Section: Data Sourcesmentioning
confidence: 99%